(untitled) (Nigerian Journal of Technology, 2016)
In Ondo State, some businesses, telecommunication agencies and government agencies are not utilizing Information Technology (IT) services to its maximum due to challenges faced by IT penetration in the state. This paper presents the design of a Government Cloud (G-Cloud) network for Ondo State Government which will provide Infrastructure as a Service (IaaS) and Software as Service (SaaS) to major government establishments and citizens within Ondo State. In designing the G-Cloud a mathematical model of cloud computing data center was adapted to design the network; and specifications from cloud management software were used to deploy the (AMD)-Virtualized server. The simulation results from CloudAnalyst and Cloudsim show that utilizing one data center with 50Vitual Machines (VMs) the response time is 201.10ms and on increasing the number of data center to five with 50VMs per data center, the response time reduced to 56.10ms. The paper proposes a G- Cloud with five data centers that can be adopted by the state government to close the digital divide gap, or a start-up G-Cloud with one data center at a lower cost. http://dx.doi.org/10.4314/njt.v35i3.20